2016
DOI: 10.1111/josl.12212
|View full text |Cite
|
Sign up to set email alerts
|

What the signs say: Gentrification and the disappearance ofcapitalism without distinctionin Brooklyn

Abstract: We examine shop signs in Brooklyn, New York, as sociolinguistic technologies of place-making that operate through specific language ideologies which represent class struggles for material wealth. We find two salient types of signs which we call Old School Vernacular and Distinction-making signage. The first indexes multiple inclusions in the neighborhood economy before gentrification and thus suggests a capitalism without distinction. These signs also challenge linguistic and literacy prescriptivism. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 36 publications
(28 reference statements)
0
46
0
Order By: Relevance
“…Elsewhere, we have identified and described the features of the two distinct and salient styles of storefront signage (Trinch & Snajdr, 2017). Old School Brooklyn Vernacular, which represents pre-gentrified Brooklyn, is everywhere throughout the borough and is most prevalent in our data.…”
Section: Signs Of the Hood (Or Nabe)mentioning
confidence: 99%
See 2 more Smart Citations
“…Elsewhere, we have identified and described the features of the two distinct and salient styles of storefront signage (Trinch & Snajdr, 2017). Old School Brooklyn Vernacular, which represents pre-gentrified Brooklyn, is everywhere throughout the borough and is most prevalent in our data.…”
Section: Signs Of the Hood (Or Nabe)mentioning
confidence: 99%
“…We have found that this type of sign in its Brooklyn New School manifestation is actually not so pleasing to some residents and consumers in the neighborhood. In addition to textual brevity (and arguably wit), these New School signs contain sociolinguistic features that indicate, following the work of Bourdieu (1990), a distinction-making exclusivity and the exclusion and gating of certain publics (Trinch & Snajdr, 2017). The features of New School signage include polysemic or cryptic names, languages other than English (that index sophistication and worldliness, but not native speech communities), erudite historical and literary references, and ironic word play.…”
Section: Signs Of the Hood (Or Nabe)mentioning
confidence: 99%
See 1 more Smart Citation
“…The handiwork behind some dishes is as simple as a 5sauté pan, butter and a few accents and herbs. Aside from the obvious matter‐of‐factness of the restaurant's name (cf. Trinch and Snajdr ), note the critic's positive evaluation of ‘not [trying] too hard’ (line 1) and of being ‘humble in reach’ (line 2). This is the effortlessness I mention above, or rather, it is the guise of effortlessness.…”
Section: The Discourse Of Elite Authenticitymentioning
confidence: 99%
“…As a contemporary site of gentrification, Brooklyn has been of increasing sociolinguistic interest in recent years (e.g. Trinch and Snajdr 2017). Historically a borough of immigrants, it has been named the fifth most expensive city (for residents) in the U.S., 7 and additionally experienced a so-called 'culinary renaissance' (LeBesco and Naccarato 2015).…”
Section: Data Selectionmentioning
confidence: 99%